Čhotmāihēt Phrabāt Somdet Phraparaminthra Mahā Phūmiphon ʻAdunlayadēt kap Wat Phra Chētuphonwimonmangkhalārām : nư̄angnai wan khlāi wan phrabo̜rommarātchasomphop Phrabāt Somdet Phraparaminthra Mahā Phūmiphon ʻAdunlayadēt 5 Thanwākhom 2559 = The chronicle of King Bhumibol Adulyadej and Wat Po : on His Majesty's birthday 5th December 2016 - Sānti Phakdīkham (Wat Phra Chētuphonwimonmangkhalārām, 2017)
On King Bhumibol Adulyadej of Thailand, 1927-2016, and his visits to Wat Phrachetuphon.